Cat-CVD SiNx as a gas barrier for application to perovskite solar cells. (1st December 2022) - Tu, Huynh Thi Cam; Shimazaki, Ai; Kaneko, Ryuji; Wakamiya, Atsushi; Ohdaira, Keisuke
Abstract: We investigated a silicon nitride (SiN x ) film prepared by catalytic chemical vapor deposition as a gas barrier for further improving stability of mixed-cation-halide perovskite (PVK) Cs0.05 FA0.85 MA0.1 PbI2 Br under dark air conditions. The SiN x film can be formed on the PVK capped with carrier transport layers such as 2, 2′, 7, 7′-tetrakis[N, N-di(4-methoxylphenyl)amino]−9, 9′-spirobifluorene (Spiro-OMeTAD) and phenyl-C61 -butyric-acid-methyl-ester (PCBM)/aluminum-doped-zinc-oxide (AZO) with less degradation in its optical transmittance property and crystal structure. The PVK/Spiro-OMeTAD encapsulated by SiN x exhibits a slower reduction in average carrier lifetime after storage for 330 h at room temperature with ∼65%RH. The PVK/PCBM/AZO covered with SiN x shows a small blue-shift (8–10 nm) in the absorption band-edge of PVK and with less decrease in the transmittance in the long wavelength range for ∼500 h at 85 °C with ∼2%RH. These results demonstrate the effect of SiN x in preventing the degradation of PVK due to the interactions with moisture and oxygen in the air.